2015
DOI: 10.1016/j.jcm.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation in the Treatment of Plantar Digital Neuralgia: A Retrospective Study of 38 Cases

Abstract: Objective: The purpose of this retrospective case series is to describe treatment outcomes for patients with plantar digital neuralgia (PDN) (Morton's neuroma) who were treated using foot manipulation. Methods: Charts were reviewed retrospectively for patients with a diagnosis of PDN and who received a minimum of 6 treatments consisting of manipulation alone. Visual analogue pain scales (VAS) and pressure threshold meter readings (PTM) were extracted as outcome measures. Results: Thirty-eight cases met inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…Confusion surrounds the name MN, with many alternative descriptions for the condition (e.g. intermetatarsal neuroma [5, 19], intermetatarsal neuritis [5], plantar interdigital neuroma [1, 7, 20], interdigital neuroma [3, 4, 10, 21], interdigital neuralgia [22], interdigital neuritis [23] and plantar digital neuralgia [2]) and no histological evidence of a true neuroma with axonal degeneration and collagen proliferation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Confusion surrounds the name MN, with many alternative descriptions for the condition (e.g. intermetatarsal neuroma [5, 19], intermetatarsal neuritis [5], plantar interdigital neuroma [1, 7, 20], interdigital neuroma [3, 4, 10, 21], interdigital neuralgia [22], interdigital neuritis [23] and plantar digital neuralgia [2]) and no histological evidence of a true neuroma with axonal degeneration and collagen proliferation [24].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is the most common neuropathy after carpal tunnel syndrome. 3 A recent sys tematic review concluded that support for non-operative and operative management consisted of low-quality research and sample sizes or of poorly controlled case series. 1 The current podiatrist clinical practice guidelines do not include manual therapy or physiotherapy as a treat ment option before surgical intervention to manage MN.…”
mentioning
confidence: 99%
“…Chiropractic and podiatric literature have reported success within this population in application of passive manual interventions, such as manipulation, to provide short-term relief of patient's symptomatic complaints [4,13]. A PT reported a single-case following a similar approach to describe short-term reductions in painpressure threshold testing [22].…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review concluded that results of conservative care are so poor that initial treatment should be surgery [1]. Although surgery is generally accepted as a gold-standard first line of treatment, podiatrists contend that there is no convincing evidence that surgery results in better patient outcomes than conservative care [4]. Surgery has resulted in variable success (62-83%) and is dependent upon accurate diagnosis as there is a potential for excision of asymptomatic interdigital nerves [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation